Escaping Our Shitty Reality: Counterpublics, Orange Is the New Black, and Religion - Shoemaker, Terry (Journal of religion and popular culture, 2017)
Recognizing popular culture as an increasingly valuable discursive site, this article argues that Orange Is the New Black, the popular Netflix series, intentionally attempts to operate as a counterpublic discursive engagement to challenge tacitly held opinions about female prisoners and the carceral system of the United States. To unfold this counterpublic discourse, this article explores the utility of religion within the third season of Orange Is the New Black as a means of constructing the counterpublic. Through characters of the series using religion as a creative means of resistance, consumers of the series come to understand the humanity of female prisoners, the complexity of prisoner narratives, and the injustice of the American carceral system. At the end, I explore why religion might be a space of creative agency for depictions pertaining to the American carceral system.